HSV presence in brains of individuals without dementia: the TASTY brain series - Jan Olsson; Hugo Lövheim; Emma Honkala; Pekka J. Karhunen; Fredrik Elgh; Eloise H. Kok (The Company of Biologists, 2016)
Herpes simplex virus (HSV) type 1 affects a majority of the population and recent evidence suggests involvement in Alzheimer's disease aetiology. We investigated the prevalence of HSV type 1 and 2 in the Tampere Autopsy Study (TASTY) brain samples using PCR and sero-positivity in plasma, and associations with Alzheimer's disease neuropathology. HSV was shown to be present in human brain tissue in 11/584 (1.9%) of samples in the TASTY cohort, of which six had Alzheimer's disease neuropathological amyloid beta (Aβ) aggregations. Additionally, serological data revealed 86% of serum samples tested were IgG-positive for HSV. In conclusion, we report epidemiological evidence of the presence of HSV in brain tissue free from encephalitis symptoms in a cohort most closely representing the general population (a minimum prevalence of 1.9%). Whereas 6/11 samples with HSV DNA in the brain tissue had Aβ aggregations, most of those with Aβ aggregations did not have HSV present in the brain tissue.